Save Soils from Irrigation - Chahal, S.S. (Journal of Soil and Water Conservation, 2022)
For raising food or other crops an adequate and timely supply of water is necessary even for the best of soils. Different crops need different watering regimes., The crop pattern of a tract, among other factors, is ordinarily governed by the soil characteristics and the available water supplies. Regulation of the availability of water in the soils, can be done by draining out the excess free water, or by providing irrigation water to soils with deficient available moisture.The situation, size and topography of our country are responsible for a very peculiar pattern of rainfall in different parts of the country. Major part of the annual precipitation is received all over the country except the Southern parts of the Eastern coast, in a period of about 21 to 3 months of the monsoons. This rainy season is preceded and followed by periods of prolonged and extreme drought. In the North Western parts and in the southern parts of the Eastern Coast, there are again a few showers during the winter months. In short bright and sunny days are _ more numerous than wet days, almost all over the country. Also the rainfall is eratic both in intensity and distribution. The intensity 0:' rainfall is usually heavy to very heavy. Drizzles or light showers are very few. Either the land remains dry or it is flooded.